2013
DOI: 10.1007/s10880-013-9383-y
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Interviewing Promotes Adherence and Improves Wellbeing in Pre-Dialysis Patients with Advanced Chronic Kidney Disease

Abstract: Low rates of adherence to medical treatments and adverse emotional states are a widespread problem in advanced chronic kidney disease (ACKD). Motivational interviewing using the stages of change model is an effective combination in promoting behavior modifications. The objective of the present study was to determine the effectiveness of an individual, pre-dialysis intervention program (monthly sessions of 90 min over a 6-month period) in terms of adherence, emotional state and health-related quality of life (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 45 publications
2
15
0
5
Order By: Relevance
“…Keeping in mind the time period of the data collection, the cause of this effect in the control group was owed to changes in nutrition resulting from the beginning of the summer. Only a few studies assess the effect of MI on treatment adherence in HD or advanced CKD patients (Crown et al, 2017;García-Llana et al, 2014;Russel et al, 2011). The study of Russel et al (2011) found an improvement in participation to HD but a deterioration in fluid intake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Keeping in mind the time period of the data collection, the cause of this effect in the control group was owed to changes in nutrition resulting from the beginning of the summer. Only a few studies assess the effect of MI on treatment adherence in HD or advanced CKD patients (Crown et al, 2017;García-Llana et al, 2014;Russel et al, 2011). The study of Russel et al (2011) found an improvement in participation to HD but a deterioration in fluid intake.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the studies in the literature dealt with the impact of motivational interview on treatment adherence and the quality of life for the patients that received HD treatment (Crown et al, 2017;Russel et al, 2011) and advanced CKD patients (García-Llana et al, 2014). However, these studies were designed as pretest-posttest and their findings did not support each other.…”
Section: Introductionmentioning
confidence: 99%
“… 16 Motivational interviewing, a counseling style that engages patients’ motivational drive to change behavior, increases adherence and well-being in patients with CKD. 74 - 76 …”
Section: Reviewmentioning
confidence: 99%
“…Motivational interviewing also has been used to improve adherence to treatment for chronic kidney disease, with a defined protocol describing the use of MI as an adjunct to chronic kidney disease treatment to improve self-management (Martino, 2011;Sanders, Whited, & Martino, 2013). In one study, following an MI intervention delivered as monthly 90-minute sessions over 6 months, patients with chronic kidney disease demonstrated greater treatment adherence, lower levels of depression and anxiety, increased healthrelated quality of life, and better-controlled biochemical parameters, compared to their own preintervention baseline (Garcia-Llana, Remor, del Peso, Celadilla, & Selgas, 2014).…”
Section: Motivational Interviewing and Management Of Chronic Diseasementioning
confidence: 99%